Early precursors of low attention and hyperactivity in moderately and very preterm children at preschool age - M. Regina Morales; Concetta Polizzi; Giorgio Sulliotti; Claudia Mascolino; Giovanna Perricone (MDPI AG, 2013)
The low attention and hyperactivity are major morbidities associated with very and moderately preterm birth. The study has been aimed at investigating the likely occurrence of early precursors of Attention Deficit and Hyperactivity Disorder (ADHD) in very and moderately preterm children at preschool age. The involved children were: 25 very preterm children (M=29.4 weeks of gestational age, SD=2), with low birth weight (M=1200 g, SD=250 g); 35 moderately preterm children (M=34.6 weeks of gestational age, SD=1) with low birth weight (M=2100 g, SD=250 g); 60 healthy full-term children as the control group. Parents of children have been administered specific questionnaires to detect low attention and hyperactivity of their children at home. The data have shown the risk of precursors of ADHD, highlighting statistically significant birth-related differences in both hyperactivity/impulsivity [F(2,119)=3.5, P=0.03, η2=0.06] and inattention [F(2,119)=2.4, P=0.04, η2=0.04], where very preterm children have got higher scores in these two dimensions compared with full-term and moderately preterm children. The very preterm children have got higher scores of impulsivity and inattention than the full-term children (Tukey'HSD − Honestly Significant Difference; P<0.001).